Comparative Structural and Functional Analyses of the Fusiform, Oval, and Triradiate Morphotypes of Phaeodactylum tricornutum Pt3 Strain - Galas, Ludovic; Burel, Carole; Schapman, Damien; Ropitaux, Marc; Bernard, Sophie; Bénard, Magalie; Bardor, Muriel (Frontiers in Plant Science, 2021)
The diatom Phaeodactylum tricornutum is a marine unicellular microalga that exists under three main morphotypes: oval, fusiform, and triradiate. Previous works have demonstrated that the oval morphotype of P. tricornutum Pt3 strain presents specific metabolic features. Here, we compared the cellular organization of the main morphotypes of the diatom P. tricornutum Pt3 strain through transmission electron and advanced light microscopies. The three morphotypes share similarities including spectral characteristics of the plastid, the location of the nucleus, the organization of mitochondria around the plastid as well as the existence of both a F-actin cortex, and an intracellular network of F-actin. In contrast, compared to fusiform and triradiate cells, oval cells spontaneously release proteins more rapidly. In addition, comparison of whole transcriptomes of oval versus fusiform or triradiate cells revealed numerous differential expression of positive and negative regulators belonging to the complex dynamic secretory machinery. This study highlights the specificities occurring within the oval morphotype underlying that the oval cells secrete proteins more rapidly.